Seleksi Lima Isolat Fungi Mikoriza Arbuskular untuk Pembibitan Kelapa Sawit (Elaeis guineensis Jacq.) pada dua Dosis Pupuk NPK - Retta Ramadhina Rias; Maria Viva Rini; Fitri Yelli (Politeknik Negeri Lampung., 2015)
Oil palm (Elaeis guineensis Jacq.) in Indonesia commonly cultivated on land that is classified as marginal land such as soil type ultisol with a low fertility rate, so it is necessary to improve the quality of seeds with the use of arbuscular mycorrhiza fungi (AMF) and NPK fertilizers. This study aimed (1) to determine the most appropriate type of AMF for oil palm seedling, (2) to determine the dose of NPK fertilizeris best for the growth of oil palm seedlings, (3) to determine whether the response of oil palm seedling stobe determined by the type of NPK fertilizer, (4) to determine the best dose of NPK fertilizer for each type of AMF. Research compiled using factorial treatment design (6 x2) with 5 replications. The first factor is the type of mycorrhizal (M) which consists of 6 levels iem0 (without AMF), m1 (Entrophospora sp. Isolates MV 3 ), m2 (Entrophospora sp. Isolates MV12), m3 (Glomus sp. Isolates MV 4), m4 (Glomus sp. Isolates MV11), and m5 (Glomus sp. Isolates MV13). The second factoris the dose of NPK fertilizer (P) which consists of 2 level p1 (100% of the recommended dose), p2 (75% of the recommended dose). The similarity of variance between treatments were tested with Least Significant Differencetest (LSD) at 5% significance level . The results showed (1) All types of FMA being tested can increase the growth of oil palm seedlings compared without exception AMF Glomus sp. MV isolates 11, (2) dose of NPK fertilizer 100% of recommended doses produce the best growth of oil palm seedlings shown by the fresh weight of shoot, dry weight of shoot, fresh weight of root, dry weight of root,and leaf greenness level, (3) palm seedling growth response to AMF inoculationis not determined by a given dose of NPK fertilizer, (4) there is no optimum dose of NPK fertilizer for each type of AMF were used. Keywords :Arbuscular mycorrhizal fungi, dose NPK fertilize, oil palm seedling.